2013
DOI: 10.2527/jas.2013-6233
|View full text |Cite
|
Sign up to set email alerts
|

TRIENNIAL REPRODUCTION SYMPOSIUM: The ovarian follicular reserve in cattle: What regulates its formation and size?1,2

Abstract: The ovarian follicular reserve has been linked to fertility in cattle. Young adult cattle with low vs. high numbers of antral follicles ≥ 3 mm in diameter in follicular waves also have fewer preantral follicles and decreased fertility. This underscores the importance of understanding the factors that regulate early follicular development and establish the ovarian follicular reserve, but little is known about how the follicular reserve is first established. In ruminants and humans, follicles form during fetal l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 36 publications
0
19
0
2
Order By: Relevance
“…From Edson et al, 2009;Jagarlamudi et al, 2010;Baillet and Mandon-Pépin, 2012;Monget et al, 2012;Pelosi et al, 2015. In addition, some somatic cell-derived factors play important roles in cyst breakdown. Indeed, estradiol signaling is critical for inhibiting this process until birth in rodents (Chen et al, 2007) and may regulate it in ruminants as well (Fortune et al, 2010(Fortune et al, , 2013. In mouse, growth factors such as activin/follistatin and neurotrophins also influence cyst breakdown and the size of the primordial follicle pool (Bristol-Gould et al, 2006;Kerr et al, 2009;Kimura et al, 2011), and recently the disintegrin Adam10 has been shown to govern the recruitment of the pregranulosa cells in cysts (Feng et al, 2016).…”
Section: Molecular Controlmentioning
confidence: 99%
“…From Edson et al, 2009;Jagarlamudi et al, 2010;Baillet and Mandon-Pépin, 2012;Monget et al, 2012;Pelosi et al, 2015. In addition, some somatic cell-derived factors play important roles in cyst breakdown. Indeed, estradiol signaling is critical for inhibiting this process until birth in rodents (Chen et al, 2007) and may regulate it in ruminants as well (Fortune et al, 2010(Fortune et al, , 2013. In mouse, growth factors such as activin/follistatin and neurotrophins also influence cyst breakdown and the size of the primordial follicle pool (Bristol-Gould et al, 2006;Kerr et al, 2009;Kimura et al, 2011), and recently the disintegrin Adam10 has been shown to govern the recruitment of the pregranulosa cells in cysts (Feng et al, 2016).…”
Section: Molecular Controlmentioning
confidence: 99%
“…The robust decrease in follicle number reported is associated with increased maternal testosterone during dietary restriction and was independent of calf birthweight and postnatal growth. Further, in vitro data suggest that ovarian steroids are potent negative regulators of follicle formation and, as such, environmental factors that alter steroid production in the dams and/or fetus may affect the size of the ovarian follicle reserve (Fortune et al 2013).…”
Section: Female Offspring: Cattlementioning
confidence: 99%
“…Besides, in bovine ovaries, the first primary and secondary follicles were observed around 140 and 210 dpc, respectively. No secondary follicles were observed in the fetal human ovary [30]. In pig, primordial follicle formation was observed between 70 and 90 dpc, while primordial to primary follicle transition was between 90 dpc and postnatal day 1 [31].…”
Section: The Role Of Androgens and Estrogens In The Ovarian Developmentmentioning
confidence: 93%